#TITLE_ALTERNATIVE# - M. TAMBUNAN (NIM 12104088); Pembimbing : Dr. Eng. Syafrizal, ST., MT., DARWIN
Reserve calculation is an important stage in quantifying the existence of mineral sediment (coal or ore). The calculation has to be in an optimal result, in which there is no bias with the error level and does not exceed the accountable criteria. Detailed research was performed in Pit-4 PT KPP, Tanjung Alam, South Kalimantan. Execution of modelling and calculation of reserve are using Minescape 4.115c and comparison of reserve calculation using vertical section method is performed. Reserve modelling and calculation are performed on 6 seams consist of Group Seam C (Seam C, C Upper, and C Lower) and Group Seam D (Seam D, D Upper, and D Lower). The result of modelling on those seams indicates that the position of coal seam in examination area has relative strike direction of North East-South West and dip direction within South East-North West direction. Calculation of reserve on examination area results on: The result of resource calculation which is measured on seam Group C with Minescape 4.115c is 6.220.319 ton with broad of area of 137.41 ha. The result of coal tonnage using vertical section method on seam Group C is 1.925.512 ton and overburden volume in amount of 13.048.685 bcm resulting on Stripping Ratio of 6,7. The result of coal tonnage with Minescape 4.115c on Group seam C is 1.926.537 ton and overburden volume in amount of 13.228.150 bcm resulting on Stripping Ratio of 6,8. Whereas the calculation of seam group C and D results on coal tonnage of 2.230.083 ton and overburden volume in amount of 16.961.740 bcm resulting Stripping Ratio of 7,6.